Polychloroprene latex adhesive, polychloroprene latex adhesive for polyolefin resin adhesion, joined body, and method for manufacturing joined body
By incorporating a tackifying resin emulsion and a pH adjuster into the chloroprene polymer latex, the polychloroprene latex adhesive achieves enhanced sprayability, reduced drying time, and strong adhesion to polyolefin resins, addressing the challenges faced by existing adhesives.
Patent Information
- Application Number
- JP2023210125
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2023-12-13
- Publication Date
- 2025-04-10
AI Technical Summary
Polychloroprene latex adhesives face challenges in achieving excellent sprayability, shortening drying time, and maintaining strong adhesion to polyolefin resins, especially when in a wet state.
The addition of a specific tackifying resin emulsion and a pH adjuster, such as organic acids, to the chloroprene polymer latex, while maintaining a pH and mechanical stability within a specific range, enhances the adhesive properties and sprayability of the polychloroprene latex adhesive.
This solution results in a polychloroprene latex adhesive with improved sprayability, reduced drying time, and excellent adhesion to polyolefin resins, even in a wet state, making it suitable for bonding polyolefin resins and nonwoven fabrics.
Smart Images

Figure 2025060354000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polychloroprene latex adhesive, a polychloroprene latex adhesive for bonding polyolefin resins, a bonded body, and a method for producing a bonded body. [Background technology]
[0002] Polychloroprene latex is used in a variety of fields, including as water-based adhesives for civil engineering and construction, plywood, furniture, shoes, wetsuits, etc., as dip-molded products for work gloves, laboratory gloves, medical gloves, balloons, etc., and as waterproof coatings for civil engineering and construction, etc. Of these, water-based adhesives (polychloroprene latex adhesives) are highly safe because they are water-based, and are actively being investigated for various applications due to their wide range of adaptability to adherends and good balance of adhesive properties.
[0003] Polyolefin resins are water-resistant and chemical-resistant, and are lightweight and strong, and therefore are widely used as materials for various molded products such as automobile interior materials, electrical insulating materials, and everyday sundries, but they are extremely difficult to bond to substances such as polyolefin resins, which have no polar groups on their surfaces and have low polarity. In addition, if polyolefin resins and the like cannot be bonded, there is a problem that the products and manufacturing processes to which polychloroprene latex adhesives can be applied are greatly limited.
[0004] Generally, polychloroprene latex adhesives are applied to both adherends to be joined, and then the adhesive layers are dried before lamination, resulting in high adhesiveness immediately after lamination. Due to these characteristics, it is expected to be used as a water-based contact adhesive, but there are problems such as the need for drying time, which means that it takes time to bond the adhesive after application, and the need for special drying equipment to shorten the drying time, which leads to increased costs.
[0005] As a means for improving adhesion to polyolefin resins, a chloroprene rubber latex adhesive in which a chlorinated polyolefin resin emulsion is added to a chloroprene polymer latex is known (see, for example, Patent Document 1).
[0006] Furthermore, polychloroprene latex adhesives are often applied to adherends by spraying, and therefore are required to have sprayability. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2018 / 043586 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a polychloroprene latex adhesive which has excellent sprayability, shortens the drying time of the adhesive layer when the adhesive is used, and has excellent adhesive strength with polyolefin resin even in a wet state. [Means for solving the problem]
[0009] Means for Solving the Problems The present inventors have conducted extensive research and found that the above-mentioned objects can be achieved by a polychloroprene latex adhesive having pH and mechanical stability within predetermined ranges by adding a specific tackifier resin emulsion and a specific pH adjuster to a chloroprene polymer latex.
[0010] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. [1] A polychloroprene latex adhesive comprising a chloroprene polymer latex, a tackifier resin emulsion, and a pH adjuster, the polychloroprene latex adhesive contains the tackifier resin emulsion in an amount of 1 to 100 parts by mass in terms of solid content when the chloroprene polymer latex contained in the polychloroprene latex adhesive is taken as 100 parts by mass in terms of solid content, and the pH adjuster is an organic acid; The pH of the polychloroprene latex adhesive is 7 to 10; When the polychloroprene latex adhesive is adjusted to a solid content concentration of 53% by mass to obtain a test polychloroprene latex adhesive, a shear force of 1.0 kg load and 1000 rpm rotation speed is applied to the test polychloroprene latex adhesive using a Marlon testing device for 2 minutes to generate aggregates, the generated aggregates are collected on a SUS80 mesh wire screen, washed with pure water, dried under reduced pressure, and the mass is measured, and the aggregate generation rate calculated by the following formula is 1 to 20%. Aggregate generation rate (%) = dry mass of aggregates [g] / solid mass of test polychloroprene latex adhesive [g] × 100 Polychloroprene latex adhesive. [2] The polychloroprene latex adhesive according to [1], wherein the chloroprene polymer latex has a toluene-insoluble content of 20 mass% or less. [3] The polychloroprene latex adhesive according to [1] or [2], wherein the tackifier resin emulsion contains one or more resins selected from the group consisting of rosin-based resins, terpene phenol-based resins, alkylphenol-based resins, and petroleum-based resins. [4] The polychloroprene latex adhesive according to any one of [1] to [3], wherein the pH adjuster comprises one or more selected from the group consisting of hydroxy acids, boric acid, and amino acids. [5] The polychloroprene latex adhesive according to any one of [1] to [4], wherein the pH adjuster is contained in an amount of 0.1 to 30 parts by mass, calculated as a solid content, relative to 100 parts by mass of the chloroprene polymer latex contained in the polychloroprene latex adhesive, calculated as a solid content. [6] The polychloroprene latex adhesive according to any one of [1] to [5], containing a plasticizer in an amount of 0.1 to 100 parts by mass, calculated as a solid content, relative to 100 parts by mass of the chloroprene polymer latex contained in the polychloroprene latex adhesive, calculated as a solid content. [7] The polychloroprene latex adhesive according to any one of [1] to [6], wherein at least one of the adherends is a polyolefin resin. [8] The polychloroprene latex adhesive according to any one of [1] to [7], wherein one of the adherends is a polyolefin resin, and the other of the adherends is a nonwoven fabric. [9] A bonded body comprising an adherend made of a polyolefin resin and an adherend made of a nonwoven fabric bonded together with the polychloroprene latex adhesive according to any one of [1] to [8].
[10] A method for producing a bonded body, comprising: a coating step, a drying step, and a bonding step, in which the polychloroprene latex adhesive according to any one of [1] to [8] is coated on at least one of adherends in the coating step; the adherend coated with the polychloroprene latex adhesive is left for a predetermined period of time in the drying step; and the bonded body is formed by bonding the adherend that has been left for the predetermined period of time to another adherend, the predetermined period of time being greater than or equal to 1 minute and less than 10 minutes. Effect of the Invention
[0011] According to the present invention, a polychloroprene latex adhesive can be obtained which has excellent sprayability, shortens the drying time of the adhesive layer when the adhesive is used, and has excellent adhesive strength with polyolefin resin even in a wet state. The polychloroprene latex adhesive of the present invention is particularly suitable for use as a spray-type adhesive used for bonding polyolefin resin and nonwoven fabric. In the method for producing a bonded body using the polychloroprene latex adhesive of the present invention, the long-term drying or heat drying required in the conventional method is not essential, so that the work process can be shortened, energy and costs can be reduced, and the equipment can be simplified. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. Note that the embodiment described below is an example of a typical embodiment of the present invention, and the present invention is not limited thereto.
[0013] The polychloroprene latex adhesive according to the present invention contains a chloroprene polymer latex (a), a tackifier resin emulsion (b), and a pH adjuster (c). Hereinafter, components that may be contained in the polychloroprene latex adhesive according to the present invention will be described.
[0014] 1. Chloroprene polymer latex (a) The chloroprene polymer latex according to the present invention contains a chloroprene polymer. The chloroprene polymer in the present invention means a polymer containing a monomer unit derived from 2-chloro-1,3-butadiene (hereinafter referred to as a chloroprene monomer), and includes a homopolymer of a chloroprene monomer and a copolymer containing a monomer unit derived from a chloroprene monomer and another monomer copolymerizable with the chloroprene monomer. Examples of the other monomer include 1-chloro-1,3-butadiene, 2,3-dichloro-1,3-butadiene, butadiene, isoprene, styrene, acrylonitrile, sulfur, acrylic acid and its esters, methacrylic acid and its esters, etc.
[0015] The chloroprene polymer latex according to one embodiment of the present invention preferably contains 60 to 100% by mass of chloroprene monomer units when the chloroprene polymer contained in the chloroprene polymer latex is taken as 100% by mass. The content of the chloroprene monomer units is, for example, 60, 65, 70, 75, 80, 85, 90, 95, 99, or 100% by mass, and may be within a range between any two of the numerical values exemplified here.
[0016] The chloroprene polymer latex according to one embodiment of the present invention may contain a monomer unit derived from an ethylenically unsaturated carboxylic acid, and when the chloroprene polymer contained in the chloroprene polymer latex is taken as 100% by mass, the content of the monomer unit derived from an ethylenically unsaturated carboxylic acid may be 0 parts by mass or more and less than 2 parts by mass. The content of the monomer unit derived from an ethylenically unsaturated carboxylic acid may be, for example, 0 parts by mass, 0.1 parts by mass, less than 0.2 parts by mass, 0.2 parts by mass, 0.3 parts by mass, less than 0.4 parts by mass, 0.4 parts by mass, 0.5 parts by mass, 0.8 parts by mass, 1.0 parts by mass, 1.5 parts by mass, or less than 2.0 parts by mass, and may be within a range between any two of the numerical values exemplified here. The chloroprene polymer latex according to one embodiment of the present invention may not contain a chloroprene polymer containing a monomer unit derived from an ethylenically unsaturated carboxylic acid.
[0017] The chloroprene polymer latex according to one embodiment of the present invention may contain one kind of chloroprene polymer, or may contain two or more kinds of chloroprene polymers. When the chloroprene polymer latex according to one embodiment of the present invention contains two or more kinds of chloroprene polymers, it is preferable that the total content of each monomer unit contained in the two or more kinds of chloroprene polymers contained in the chloroprene polymer latex is within the above-mentioned numerical range.
[0018] The chloroprene polymer latex according to one embodiment of the present invention preferably contains a homopolymer of a chloroprene monomer. The chloroprene polymer latex according to one embodiment of the present invention preferably contains more than 50% by mass and not more than 100% by mass of a homopolymer of a chloroprene monomer, more preferably more than 80% by mass and not more than 100% by mass, and more preferably more than 90% by mass and not more than 100% by mass, based on 100% by mass of the solid content of the chloroprene polymer latex contained in the polychloroprene latex adhesive. The content of the homopolymer of a chloroprene monomer may be, for example, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100% by mass, and may be within a range between any two of the values exemplified here.
[0019] The chloroprene polymer latex according to one embodiment of the present invention may contain a carboxy-modified chloroprene copolymer, and may contain 0% or more and less than 50% by mass of the carboxy-modified chloroprene copolymer, based on 100% by mass of the solid content of the chloroprene polymer latex contained in the polychloroprene latex adhesive, or 0% or more and less than 20% by mass, or 0% or more and less than 10 parts by mass. The content of the carboxy-modified chloroprene copolymer may be, for example, 0, 5, 10, 15, 20, 25, 30, 35, 40, 45% by mass, or less than 50% by mass, and may be within a range between any two of the numerical values exemplified here. The chloroprene polymer latex according to one embodiment of the present invention may not contain a carboxy-modified chloroprene copolymer.
[0020] <Toluene insolubles> The chloroprene polymer latex according to the present invention preferably has a toluene-insoluble content of 20% by mass or less. In the present invention, the toluene insoluble content refers to the content of gel content in the chloroprene polymer that is insoluble in toluene solvent. Also, the sol refers to a component that is soluble in toluene solvent. It is expected that the chloroprene polymer containing a large amount of sol with excellent molecular mobility will facilitate fusion of the chloroprene polymer molecular chains at the adhesive interface (prone to moderately aggregate), which can contribute to the development of initial adhesive strength and adhesive strength in a wet state, and will facilitate the development of adhesive strength.
[0021] The toluene insoluble content is more preferably 10% by mass or less, for example, 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 16%, 18%, 20% by mass, and may be within a range between any two of the values exemplified here. In one embodiment, the toluene insoluble content may be less than 8% by mass, and is preferably less than 3% by mass. If the gel content of the chloroprene polymer exceeds 20% by mass, the initial adhesive strength and the adhesive strength in a wet state decrease, which is undesirable.
[0022] The toluene insoluble matter can be calculated by the following formula, where Ag is the mass of a dried product obtained by freeze-drying a chloroprene polymer latex, and Bg is the gel matter separated from a mixture obtained by dissolving the freeze-dried latex in toluene. Specifically, it can be calculated by the method described in the Examples. Toluene insolubles (gel content) = B / A x 100 (%)
[0023] The toluene insoluble matter can be controlled by adjusting the polymerization conditions during the production of the chloroprene polymer latex, for example, the types and amounts of the polymerization initiator and the chain transfer agent, as well as the production conditions such as the polymerization temperature, polymerization time, and polymerization rate.
[0024] In addition, when the chloroprene polymer latex contains two or more kinds of chloroprene polymers, it is preferable that the toluene-insoluble matter contained in the two or more kinds of chloroprene polymers (the toluene-insoluble matter of a mixture of two or more kinds of chloroprene-based polymers) is within the above-mentioned numerical range.
[0025] <Production method of chloroprene polymer latex (a)> The method for producing the chloroprene polymer latex according to the present invention is not particularly limited, but it can be produced by the following method. A method for producing a chloroprene polymer latex according to one embodiment of the present invention may include an emulsion polymerization step, in which a chloroprene monomer, or a chloroprene monomer and another monomer copolymerizable therewith, is emulsion-polymerized using an emulsifier, a dispersant, a polymerization initiator, a chain transfer agent, or the like as appropriate, and when a target polymerization rate is reached, a polymerization terminator is added to obtain a chloroprene polymer latex. From the thus obtained chloroprene polymer latex, unreacted monomers can be removed by a steam flash method, a concentration method or the like.
[0026] (emulsifier) The emulsifier is not particularly limited, and any known anionic, nonionic or cationic emulsifier used in the polymerization of chloroprene polymers can be used.
[0027] The emulsifier preferably contains one or more selected from rosin acid or its alkali metal salt. As the rosin acid, any of wood rosin acid, gum rosin acid, tall oil rosin acid, and disproportionated rosin acid obtained by disproportionating these acids can be used. When rosin acid or its alkali metal salt is used as the emulsifier, the emulsion stability of the chloroprene polymer latex is easily reduced when mechanical stimulation is applied to the chloroprene polymer latex. Therefore, when the chloroprene polymer latex is used as an adhesive, excellent initial adhesive strength can be exhibited.
[0028] When using rosin acid as an emulsifier, it is more preferable to add an alkali metal salt thereof from the viewpoint of polymerization control and initial adhesive performance, especially adhesive performance in a wet state. Examples of compounds constituting the alkali metal salt include potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate. Among these, sodium hydroxide and potassium hydroxide are preferable from the viewpoint of cost and water solubility. The amount of rosin acid added is preferably 0.5 to 10 parts by mass, more preferably 2 to 6 parts by mass, based on 100 parts by mass of the total monomers used.
[0029] In the emulsion polymerization process, anionic emulsifiers and dispersants other than rosin acid can also be used. Examples of anionic emulsifiers and dispersants other than rosin acid include alkyl sulfonates having 8 to 20 carbon atoms, alkyl aryl sulfates, condensates of sodium naphthalene sulfonate and formaldehyde, and sodium alkyl diphenyl ether disulfonate.
[0030] The emulsifier may be used in combination with a nonionic emulsifier or dispersant. By using a nonionic emulsifier in combination, the low temperature stability of the chloroprene polymer latex and the adhesiveness when used as an adhesive can be improved.
[0031] (Chain transfer agent) During emulsion polymerization of chloroprene monomers, a chain transfer agent can be added to adjust the molecular weight, molecular weight distribution, and toluene insoluble content of the chloroprene polymer. The chain transfer agent may be added at the beginning of polymerization or during polymerization. Examples of the chain transfer agent include long-chain alkyl mercaptans such as n-dodecyl mercaptan and t-dodecyl mercaptan, and dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide and diethyl xanthogen disulfide. From the viewpoint of easy control of the molecular weight and gel content, it is preferable to use long-chain alkyl mercaptans. These chain transfer agents can be used alone or in combination of two or more. The amount of the chain transfer agent added can be 0.001 to 1 part by mass with respect to 100 parts by mass of the total monomers.
[0032] (Polymerization initiator) As the emulsion polymerization initiator, a conventional radical polymerization initiator can be used, specifically, an organic or inorganic peroxide such as benzoyl peroxide, potassium persulfate, ammonium persulfate, etc., or an azo compound such as azobisisobutyronitrile, etc. A cocatalyst such as anthraquinone sulfonate, potassium sulfite, sodium sulfite, etc. may be used in combination as appropriate.
[0033] (Potassium hydroxide and sodium hydroxide) In the emulsion polymerization step, sodium hydroxide and / or potassium hydroxide can be used. The amount of sodium hydroxide and potassium hydroxide added can be 0.01 to 2.0 parts by mass based on 100 parts by mass of the monomer.
[0034] (Polymerization conversion rate) The polymerization conversion rate of the chloroprene monomer is preferably 50% by mass or more and less than 90% by mass, more preferably 60 to 85% by mass. When the polymerization conversion rate of the chloroprene monomer is less than 50%, the solid content of the chloroprene polymer latex decreases, which not only places a burden on the drying process after the adhesive application and makes it difficult to uniformize the adhesive layer, but also causes problems such as odor, adhesion, and deterioration of adhesive strength due to the residual chloroprene monomer. When the polymerization conversion rate is 90% by mass or more, the branching in the chloroprene polymer increases, and the molecular weight increases, which leads to a broadening of the molecular weight distribution, which may cause problems of deterioration of the contact property and water resistance, which are important performances in the present invention. The polymerization conversion rate (mass%) is calculated by [(polymer mass / monomer mass sum)×100].
[0035] (Polymerization temperature) Chloroprene polymers can be polymerized in the range of 0 to 45°C, but are preferably polymerized at a low temperature of 5 to 15°C. It is known that chloroprene homopolymers contain 85% or more trans-1,4-bonds, and their molecular structure is relatively regular. Chloroprene homopolymers have the properties of a typical crystalline polymer due to the high regularity of their molecular structure. By setting the polymerization temperature at a low temperature of 5 to 15°C, the ratio of trans-1,4-bonds in the polychloroprene molecule is further increased, and a chloroprene homopolymer with a higher crystallization rate can be obtained, and when this is used as an adhesive, sufficient adhesive strength is achieved.
[0036] (Polymerization terminator) In the production of chloroprene polymers, a polymerization terminator is added to terminate the reaction when a predetermined polymerization rate is reached in order to obtain a polymer with the desired molecular weight and distribution. Examples of polymerization terminators include phenothiazine, pt-butylcatechol, hydroquinone, hydroquinone monomethyl ether, and diethylhydroxylamine.
[0037] (solid content concentration) The solid content concentration of the chloroprene polymer latex is not particularly limited, but is usually 40 to 65% by mass.
[0038] 2. Tackifying resin emulsion (b) The tackifier resin emulsion is an emulsion containing a tackifier resin, which is added to improve the adhesive strength of chloroprene polymer latex adhesives, particularly when polyolefin resins are used as adherends.
[0039] The amount of the tackifier resin emulsion to be added is not particularly limited, but from the viewpoint of adhesion to an adherend, it is used in an amount of 1 to 100 parts by mass, and preferably 20 to 70 parts by mass, calculated as solid content, per 100 parts by mass of the chloroprene polymer latex calculated as solid content. The amount of the tackifier resin emulsion to be added is, for example, 0, 10, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 80, 90, or 100 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0040] The type of tackifier resin is not particularly limited, and examples thereof include rosin-based resins such as gum rosin, tall rosin, wood rosin, disproportionated rosin, polymerized rosin, glycerol esters and pentaerythritol esters of these rosins, and hydrogenated products thereof; terpene phenol-based resins such as hydrogenated products of terpene phenol resins; petroleum-based resins such as aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymerized petroleum resins, dicyclopentadiene petroleum resins, pure monomer petroleum resins, and hydrogenated products thereof; styrene-based resins; coumarone-indene-based resins; alkylphenol-based resins; xylene resins; dammar; copal; and shellac. These may be used alone or in combination of two or more. The tackifier resin preferably includes one or more selected from the group consisting of rosin-based resins, terpene phenol-based resins, alkylphenol-based resins, and petroleum-based resins. The tackifier resin more preferably includes a phenolic resin such as a terpene phenol-based resin and an alkylphenol-based resin, and even more preferably includes a terpene phenol-based resin.
[0041] Commercially available tackifier resin emulsions include terpene phenol resin emulsions such as Tamanor E-100 and Tamanor E-200NT manufactured by Arakawa Chemical Industries, Ltd.
[0042] The polychloroprene latex adhesive according to the present invention may contain a chlorinated polyolefin resin emulsion as a tackifier resin emulsion. The chlorinated polyolefin resin emulsion is a resin emulsion obtained by chlorinating a polyolefin resin.
[0043] The amount of the chlorinated polyolefin resin emulsion added is, for example, 1 to 20 parts by mass in terms of solid content relative to 100 parts by mass of the chloroprene polymer latex in terms of solid content. The amount of the chlorinated polyolefin resin emulsion added is, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20 parts by mass in terms of solid content, and may be within a range between any two of the numerical values exemplified here. From the viewpoint of adhesive strength (normal strength), it may be preferable to add a small amount of chlorinated polyolefin resin emulsion or no chlorinated polyolefin resin emulsion, and the amount is, for example, 0, 0.5, 1, 2, 3, or 4 parts by mass in terms of solid content, or less than 1 part by mass, relative to 100 parts by mass of the chloroprene polymer latex in terms of solid content.
[0044] The polyolefin in the chlorinated polyolefin resin is not particularly limited, but examples thereof include polyethylene, polypropylene, ethylene-propylene copolymer resin, ethylene-butene copolymer resin, propylene-butene copolymer resin, ethylene-propylene-butene copolymer resin, and ethylene-propylene-diene copolymer resin, with propylene-butene copolymer resin and ethylene-propylene-butene copolymer resin being preferred.
[0045] The chlorine content of the chlorinated polyolefin resin emulsion is not particularly limited, but is preferably 10 to 40% by mass. By making the chlorine content 10% by mass or more, the compatibility with the chloroprene polymer latex can be improved. In addition, by making the chlorine content less than 40% by mass, the decrease in adhesion to the adherend such as polyolefin resin can be prevented. The chlorine content is, for example, 10, 15, 20, 25, 30, 35, or 40% by mass, and may be within a range between any two of the numerical values exemplified here.
[0046] The chlorinated polyolefin resin is preferably one which is chlorinated and acid-modified, and more preferably one which is maleic anhydride-modified.
[0047] A surfactant may be added to the chlorinated polyolefin resin emulsion within a range that does not impair the effects of the present invention, and examples of such surfactants include nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants. In the present invention, a nonionic surfactant may be used from the viewpoint of improving the storage stability of the resulting polychloroprene latex adhesive.
[0048] Commercially available products that can be used as chlorinated polyolefin resin emulsions include EW-5303 and EH-801 manufactured by Toyobo Co., Ltd.
[0049] 3. pH adjuster (c) The pH adjuster is blended to improve the adhesive strength and storage stability of the chloroprene polymer latex. A weak acid or a buffer solution can be used as the pH adjuster. The pH adjuster is, for example, an organic acid, and preferably includes one or more selected from the group consisting of hydroxy acids such as citric acid and glycolic acid; boric acid; and amino acids. These can be used alone or in combination of two or more. More preferably, the pH adjuster includes at least one compound selected from amino acids. Specific examples of amino acids include glycine, alanine, threonine, and proline. In terms of cost, adhesive performance, ease of handling, and the like, it is more preferable to use glycine, which is a type of amino acid, as the pH adjuster.
[0050] The amount of pH adjuster added is not particularly limited, but it is preferable to use an amount that can adjust the pH of the chloroprene latex adhesive to a range of 7 to 10, and more preferably to a range of 8 to 10. By adjusting the pH to such a range, adhesive strength in a wet state can be obtained.
[0051] The pH of the polychloroprene latex adhesive is 7 to 10, and preferably 8 to 10. Specifically, the pH may be, for example, 7, 7.5, 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.5, or 10, and may be within a range between any two of the values exemplified here.
[0052] When glycine is used as a pH adjuster, it is preferable to use 0.1 to 30 parts by mass, preferably 0.1 to 20 parts by mass, more preferably 2 to 16 parts by mass, and even more preferably 3 to 13 parts by mass, relative to 100 parts by mass of the chloroprene polymer latex, to develop sufficient adhesive strength at advantageous costs. The amount of the pH adjuster to be added is, for example, 0.1, 1, 2, 3, 5, 10, 15, 20, 25, or 30 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0053] 4. Plasticizers (d) The polychloroprene latex adhesive may contain a plasticizer. The amount of the plasticizer added may be 0 to 20 parts by mass in terms of solid content relative to 100 parts by mass of the solid content of the chloroprene polymer latex, and from the viewpoint of initial strength, it is preferably 1 to 10 parts by mass, more preferably 2 to 8 parts by mass. The amount of the plasticizer added may be, for example, 0, 0.1, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 parts by mass, and may be within a range between any two of the numerical values exemplified here. By adding a plasticizer, the initial strength of the obtained polychloroprene latex adhesive is improved, and the texture of the adhesive film after drying can be softened. The addition of a plasticizer is expected to have the effect of improving the initial strength of the adhesive, but on the other hand, it may decrease the strength (normal strength) after a certain time (for example, one day) has passed after lamination. From such a viewpoint, the amount of the plasticizer to be added is preferably 0 to 8 parts by mass in terms of solid content relative to 100 parts by mass of the solid content of the chloroprene polymer latex. The plasticizer is preferably one having good compatibility with the chloroprene polymer, and is not particularly limited, and examples thereof include dibutyl sebacate, dibutyl phthalate, dioctyl adipate, dioctyl azelate, dioctyl sebacate, dioctyl phthalate, tricresyl phosphate, and cresyl diphenyl phosphate.
[0054] 5. Metal oxides (e) Examples of metal oxides include zinc oxide, titanium oxide, and iron oxide. These may be used alone or in combination of two or more. Commercially available zinc oxide products include AZ-SW (solid content concentration 50%), which is zinc oxide manufactured by Osaki Kogyo Co., Ltd.
[0055] The amount of metal oxide added (in terms of solid content) can be 0.1 to 5 parts by mass relative to 100 parts by mass of the adhesive. The amount of metal oxide added (in terms of solid content) can be, for example, 0.1, 0.2, 0.5, 1, 2, 3, 4, or 5 parts by mass, and may be within a range between any two of the numerical values exemplified here.
[0056] 6. Other Ingredients <Antioxidants> Polychloroprene latex adhesives are generally susceptible to deterioration due to oxygen. In the present invention, a stabilizer such as an antioxidant can be appropriately used within a range that does not impair the effects of the invention.
[0057] The amount of antioxidant added to the polychloroprene latex adhesive is preferably 0.1 to 3 parts by mass in terms of solid content per 100 parts by mass of the solid content of the chloroprene polymer latex. By setting the amount within this range, the flexibility stability over time of the obtained adhesive can be improved. When the antioxidant is insoluble in water or destabilizes the emulsified state of the chloroprene polymer latex, it is preferable to prepare the antioxidant in advance as an aqueous dispersion and then add it. The polychloroprene latex adhesive according to one embodiment of the present invention does not need to contain an antioxidant.
[0058] In addition to the above, additives such as fillers, pigments, colorants, wetting agents, defoamers, and thickeners can be appropriately used in the polychloroprene latex adhesive as long as they do not impair the effects of the present invention. The polychloroprene latex adhesive according to one embodiment of the present invention may contain polyvinyl alcohol. The content of polyvinyl alcohol may be less than 2 mass% relative to 100 mass% of the solid content of the chloroprene polymer latex contained in the polychloroprene latex adhesive, for example, 0, 0.5, 1.0, 1.5, or 2.0 parts by mass, and may be within a range between any two of the values exemplified here. The polychloroprene latex adhesive according to one embodiment of the present invention may have an improved initial adhesive strength by making the polyvinyl alcohol content equal to or less than a certain value, or by not containing polyvinyl alcohol.
[0059] In addition, the polychloroprene latex adhesive according to one embodiment of the present invention may be supplementarily blended with other resin emulsions (latexes) other than the chloroprene polymer latex (a) and the tackifier resin emulsion (b). Specific examples of other resin emulsions (latexes) include (modified) vinyl acetate, vinyl acetate-acrylic mixtures, acrylic-styrene mixtures, and urethane resin emulsions. The blending amount of other resin emulsions (latexes) may be 30% by mass or less (solid content equivalent) relative to 100% by mass of the solid content of the polychloroprene latex adhesive, and may be, for example, 0, 5, 10, 15, 20, 25, or 30% by mass, or may be within a range between any two of the numerical values exemplified here. The polychloroprene latex adhesive according to one embodiment of the present invention does not contain a chlorinated polyolefin resin emulsion, and may not contain any other resin emulsion (latex) than the chloroprene polymer latex (a), the chlorinated polyolefin resin emulsion (b-2), and the tackifier resin emulsion (b-1).
[0060] 7. Properties of Polychloroprene Latex Adhesives It is preferable that the polychloroprene latex adhesive according to one embodiment of the present invention satisfies the following adhesive strength measured by the following procedure. <Method of measuring adhesive strength (normal strength)> A nonwoven fabric (thickness 3 mm × length 180 mm × width 25 mm) and a polypropylene sheet (thickness 2 mm × length 100 mm × width 25 mm) were used as the adherends, and the adhesive was applied at 40 g / m in an atmosphere of 23°C. 2 The adhesive is sprayed onto a polypropylene sheet (application area: length 70 mm x width 25 mm) so that the adhesive is applied. After application, the adhesive is left in a 23°C atmosphere for 2 minutes (open time [OT] = 2 minutes), and the adhesive surfaces of the nonwoven fabric and polypropylene are overlapped while the adhesive is still wet (wet state), and the adherends (laminates) are pressed together using a mini test press machine (Toyo Seiki MP-WC; pressure 0.1 MPa), held for 10 seconds, and left to stand for 24 hours. Immediately after this, a 180° peel test is performed using a tensile tester (A&D Tensilon; tensile speed 200 mm / min) to measure the adhesive strength.
[0061] The polychloroprene latex adhesive according to one embodiment of the present invention has an adhesive strength (normal strength) measured by the above procedure of preferably 0.10 N / mm or more, more preferably 0.15 N / mm or more, and even more preferably 0.20 N / mm or more. The upper limit of the normal strength is not particularly limited, but is, for example, 1.00 N / mm. The normal strength may be, for example, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.30, 0.40, 0.50, or 1.00 N / mm, or may be within a range between any two of the values exemplified here.
[0062] [Mechanical stability] The polychloroprene latex adhesive according to one embodiment of the present invention has a mechanical stability (aggregate generation rate) of 1 to 20%, preferably 2 to 10, and more preferably 5 to 15. The mechanical stability (aggregate generation rate) is, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20%, and may be within a range between any two of the numerical values exemplified here. When the mechanical stability of the adhesive is equal to or higher than the above lower limit, the adhesive can be more appropriately demulsified after application and can exhibit more sufficient adhesive strength. In addition, when the mechanical stability of the adhesive is equal to or lower than the above upper limit, the adhesive can prevent deterioration of sprayability due to precipitation caused by shear caused by spraying.
[0063] The mechanical stability is a value measured by the following procedure. The polychloroprene latex adhesive is adjusted to a solids concentration of 53% by mass to obtain a polychloroprene latex adhesive for testing. A shear force of 1.0 kg load and 1000 rpm rotation speed is applied to the polychloroprene latex adhesive for testing (e.g., 50 g) for 2 minutes using a Marlon testing device to generate aggregates. The generated aggregates are collected on a SUS80 mesh wire screen, washed with pure water, dried under reduced pressure, and then their mass is measured. The aggregate generation rate is calculated from the measured dry mass of the aggregates using the following formula. Mechanical stability (aggregate generation rate) (%) = aggregate dry mass [g] / solid mass of test polychloroprene latex adhesive [g] × 100 A smaller mechanical stability value indicates greater stability against shear force. To reduce mechanical stability, the amount of pH adjuster or plasticizer added can be reduced. Mechanical stability also decreases when emulsifiers or dispersants other than cationic ones are added. On the other hand, tackifier resin emulsions tend to have larger particle sizes than chloroprene latex, so if the amount added is increased, they tend to precipitate more easily due to mechanical stimulation (shear), and mechanical stability increases.
[0064] The polychloroprene latex adhesive of the present invention described above can be used for various types of adherends, but is particularly suitable for use when the adherend is a polyolefin resin. The polychloroprene latex adhesive of the present invention shortens the drying time of the adhesive layer when the adhesive is used, and has excellent adhesive strength with polyolefin resin even in a wet state at room temperature, so that it can be used as a polychloroprene latex adhesive for bonding polyolefin resins, in which at least one of the adherends is a polyolefin resin. The polychloroprene latex adhesive according to one embodiment of the present invention can be used as a polychloroprene latex adhesive for bonding polyolefin resins, in which one of the adherends is a polyolefin resin and the other is a nonwoven fabric. The polychloroprene latex adhesive according to one embodiment of the present invention is useful for bonding polyolefin resins and nonwoven fabrics used as automobile interior materials, for example.
[0065] Moreover, a bonded body according to one embodiment of the present invention is a bonded body (for example, a laminate) in which an adherend made of a polyolefin resin and an adherend made of a nonwoven fabric are bonded together with the polychloroprene latex adhesive. Moreover, such a bonded body can be produced, for example, by a method including a coating step, a drying step, and a bonding step. In the coating step, the polychloroprene latex adhesive is applied to at least one of the adherends (it may be applied to both of them), in the drying step, the adherend to which the polychloroprene latex adhesive is applied is left for a predetermined time (it can be left at room temperature, for example, 10 to 40°C, preferably 20 to 30°C), and in the bonding step, the adherend that has been left for the predetermined time is bonded to another adherend to form a bonded body. Here, the predetermined time for leaving is 1 minute or more to less than 10 minutes, and more specifically, for example, 1, 2, 3, 4, 5, 6, 7, 8, or 9 minutes, and may be within a range between any two of the numerical values exemplified here. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples. Note that these are merely illustrative and do not limit the scope of the present invention.
[0067] <Adjustment example 1> "Production of chloroprene polymer latex a-1" Using a reactor with an internal volume of 10 liters, 90 parts by mass of water, 4.5 parts by mass of disproportionated rosin acid, 0.5 parts by mass of potassium hydroxide, and 0.3 parts by mass of sodium salt of formaldehyde naphthalene sulfonic acid condensate were charged under a nitrogen stream, and after dissolving, 100 parts by mass of chloroprene monomer and 0.1 parts by mass of n-dodecyl mercaptan were added while stirring. Potassium persulfate was used as an initiator, and polymerization was carried out at 10°C under a nitrogen atmosphere, and when the polymerization rate reached 70%, an emulsion of phenothiazine was added to terminate the polymerization. Unreacted chloroprene monomer was removed under reduced pressure, and the water was further evaporated under reduced pressure to concentrate the mixture, and the solid content concentration was adjusted to 55% by mass, to obtain a chloroprene polymer latex a-1 with a gel content of 1.9% by mass.
[0068] The gel content of the resulting chloroprene polymer was measured by the following method. [Toluene insoluble matter (gel content) measurement] The latex sample was freeze-dried and precisely weighed to obtain A(g). It was dissolved in toluene (adjusted to 0.6%) at 23°C for 20 hours, centrifuged, and the gel fraction was separated using a 200-mesh wire screen. The separated gel fraction was air-dried, then dried in an atmosphere at 110°C for 1 hour, precisely weighed, and obtained B(g). The gel fraction was calculated according to the following formula. Toluene insolubles (gel content) = B / A x 100 (%)
[0069] [Example 1] As the chloroprene polymer latex (a), 100 parts by mass of the chloroprene polymer latex a-1 obtained above was added in terms of solid content, 50 parts by mass of Tamanor E-100 (manufactured by Arakawa Chemical Industries) in terms of solid content was added as the tackifier resin emulsion (b-1), 10 parts by mass of glycine in terms of solid content was added as the pH adjuster (c), and 9 parts by mass of dibutyl sebacate in terms of solid content was added as the plasticizer (d). Water was added to adjust the solid content to 53%, thereby obtaining the polychloroprene latex adhesive of Example 1. The pH of the polychloroprene latex adhesive was 8.8.
[0070] [Example 2] As shown in Table 1, the polychloroprene latex adhesive of Example 2 was obtained under the same conditions as in Example 1, except that 1 part by mass of AZ-SW (manufactured by Osaki Kogyo Co., Ltd., solid content concentration 50%) was added as zinc oxide (e) in terms of solid content. The pH of the polychloroprene latex adhesive was 8.6.
[0071] [Example 3] As shown in Table 1, except that the plasticizer (d) was not added, the polychloroprene latex adhesive of Example 3 was obtained under the same conditions as in Example 2. The pH of the polychloroprene latex adhesive was 8.6.
[0072] [Example 4] As shown in Table 1, except that the plasticizer (d) was not added, the polychloroprene latex adhesive of Example 4 was obtained under the same conditions as Example 1. The pH of the polychloroprene latex adhesive was 8.8.
[0073] [Example 5] The polychloroprene latex adhesive of Example 5 was obtained under the same conditions as in Example 2, except that the amount of tackifier resin emulsion (b) added was changed as shown in Table 1. The pH of the polychloroprene latex adhesive was 8.6.
[0074] [Example 6] As shown in Table 1, the polychloroprene latex adhesive of Example 6 was obtained under the same conditions as in Example 1, except that 15 parts by mass of EW-5303 (manufactured by Toyobo Co., Ltd., maleic anhydride modified chlorinated ethylene-propylene-butene copolymer resin emulsion, chlorine content 17% by mass) was added as the chlorinated polyolefin resin emulsion (b-2) in terms of solid content. The pH of the polychloroprene latex adhesive was 8.7.
[0075] [Comparative Example 1] As shown in Table 1, except that the tackifier resin emulsion (b) was not added, the polychloroprene latex adhesive of Comparative Example 1 was obtained under the same conditions as in Example 1. The pH of the polychloroprene latex adhesive was 8.9.
[0076] [Comparative Example 2] As shown in Table 1, except that the pH adjuster (c) was not added, the polychloroprene latex adhesive of Comparative Example 2 was obtained under the same conditions as in Example 1. The pH of the polychloroprene latex adhesive was 12.2.
[0077] [Comparative Example 3] As shown in Table 1, except for changing the amount of tackifier resin emulsion (b) added, the polychloroprene latex adhesive of Comparative Example 3 was obtained under the same conditions as in Example 1. The pH of the polychloroprene latex adhesive was 8.7.
[0078] The polychloroprene latex adhesives obtained above were subjected to the following measurements and evaluations. Note that the compounding recipes in Table 1 are in parts by mass converted into solid content. [Mechanical stability] Each polychloroprene latex adhesive (solid content concentration: 53% by mass) was used as a test polychloroprene latex adhesive. Using a Marlon tester (Kumagaya Riki Kogyo, product number: 2312-I), the amount of aggregates generated when a shear force of 1.0 kg load and 1000 rpm rotation speed was applied to 50 g of test polychloroprene latex adhesive for 2 minutes was evaluated. After applying a shear force under the above conditions, the aggregates attached to the rotor part of the Marlon tester were collected on a SUS80 mesh wire screen, washed with pure water, dried under reduced pressure, and their mass was measured. The aggregate generation rate was calculated from the measured dry mass of the aggregates using the following formula to provide an index of mechanical stability. The smaller the aggregate generation rate, the more stable it is against shear force, indicating better mechanical stability. Aggregate occurrence rate (mechanical stability) (%) = aggregate dry mass [g] / solid mass of test polychloroprene latex adhesive [g] × 100
[0079] [Sprayability] The polychloroprene latex adhesive (adhesive) was sprayed onto an adherend (polypropylene sheet), and the sprayability (degree of clogging and adhesion of the adhesive to the adherend) was evaluated according to the following evaluation criteria. (degree of clogging) ○: No clogging and good spraying △: A little clogged, but spraying is possible ×: Spraying not possible due to clogging (Adhesive adhesion to substrate) ○: No penetration or dripping of the adhesive into the adherend is observed. △: Adhesive seeps into the adherend or drips slightly. ×: Adhesive seeps into the adherend or drips. -: Spraying was not possible due to clogging, and adhesion could not be evaluated.
[0080] [Normal strength] A nonwoven fabric (thickness 3 mm × length 180 mm × width 25 mm) and a polypropylene sheet (thickness 2 mm × length 100 mm × width 25 mm) were used as the adherends, and the adhesive was applied at 40 g / m in an atmosphere of 23°C. 2 The adhesive was sprayed onto a polypropylene sheet (application area: length 70 mm x width 25 mm) so that the adhesive was applied. After leaving it in an atmosphere of 23°C for 2 minutes (open time [OT] = 2 minutes), the adhesive surfaces of the nonwoven fabric and polypropylene were overlapped while the adhesive was still wet, and the adherend (laminate) was pressed with a mini test press machine (MP-WC, manufactured by Toyo Seiki Co., Ltd.; pressure 0.1 MPa) and held for 10 seconds, then left to stand for 24 hours (set time [ST] = 1 day). Immediately after that, a 180-degree peel test was performed with a tensile tester (Tensilon, manufactured by A&D Co., Ltd.; tensile speed 200 mm / min) to measure the adhesive strength (normal strength).
[0081] [Table 1]
[0082] As is clear from Table 1, the polychloroprene latex adhesive of the present invention has excellent sprayability and improved adhesive strength, particularly adhesive strength in a wet state (normal strength), and is therefore suitable for applications requiring excellent adhesive strength, particularly as a spray-type adhesive used for bonding polyolefin resins and nonwoven fabrics.
Claims
1. 1. A polychloroprene latex adhesive comprising a chloroprene polymer latex, a tackifying resin emulsion, and a pH adjuster, When the chloroprene polymer latex contained in the polychloroprene latex adhesive is 100 parts by mass in terms of solid content, The tackifier resin emulsion contains 1 to 100 parts by mass in terms of solid content, The pH adjuster is an organic acid, the pH of the polychloroprene latex adhesive is 7 to 10; When the polychloroprene latex adhesive was adjusted to a solids concentration of 53% by mass to obtain a test polychloroprene latex adhesive, The test polychloroprene latex adhesive is subjected to a shear force of 1.0 kg load and 1000 rpm rotation speed for 2 minutes using a Marlon testing device to generate aggregates, the generated aggregates are collected on a SUS80 mesh wire screen, washed with pure water, dried under reduced pressure, and the mass is measured, and the aggregate generation rate calculated by the following formula is 1 to 20%. Aggregate generation rate (%)=dry mass of aggregates [g] / solid mass of test polychloroprene latex adhesive [g]×100 Polychloroprene latex adhesive.
2. 2. The polychloroprene latex adhesive according to claim 1, wherein the chloroprene polymer latex has a toluene insoluble content of 20% by mass or less.
3. 3. The polychloroprene latex adhesive of claim 2, wherein the tackifier resin emulsion comprises one or more selected from the group consisting of rosin-based resins, terpene phenol-based resins, alkylphenol-based resins, and petroleum-based resins.
4. The pH adjuster includes one or more selected from the group consisting of hydroxy acids, boric acid, and amino acids.
2. The polychloroprene latex adhesive of claim 1.
5. When the chloroprene polymer latex contained in the polychloroprene latex adhesive is 100 parts by mass in terms of solid content, 0.1 to 30 parts by mass of the pH adjuster in terms of solid content, 2. The polychloroprene latex adhesive of claim 1 , comprising:
6. When the chloroprene polymer latex contained in the polychloroprene latex adhesive is 100 parts by mass in terms of solid content, 0.1 to 100 parts by mass of a plasticizer in terms of solid content, 2. The polychloroprene latex adhesive of claim 1 , comprising:
7. 7. The polychloroprene latex adhesive according to claim 1, wherein at least one of the adherends is a polyolefin resin.
8. 8. The polychloroprene latex adhesive for bonding polyolefin resins according to claim 7, wherein one of the adherends is a polyolefin resin and the other of the adherends is a nonwoven fabric.
9. 7. A bonded body comprising an adherend made of a polyolefin resin and an adherend made of a nonwoven fabric bonded together with the polychloroprene latex adhesive according to claim 1.
10. The method includes a coating step, a drying step, and a bonding step, In the coating step, the polychloroprene latex adhesive according to any one of claims 1 to 6 is coated on at least one of the adherends, In the drying step, the adherend on which the polychloroprene latex adhesive is applied is left for a predetermined period of time, In the joining step, the adherend that has been left for the predetermined time is bonded to another adherend to form a joined body, The predetermined time is from 1 minute to less than 10 minutes. A method for manufacturing a joint body.
Citation Information
Patent Citations
Chloroprene rubber latex adhesive composition
WO2018043586A1